Fungal diversity on the surface of saffron corms with different growth characteristics. (13th January 2021) - Shuwen, Han; Qing, Zhou; Jin, Liu; Miao, Da
Abstract: Saffron is one of the most expensive spices and is rich in pharmacological and biological active ingredients. We explored the community structure and diversity of the fungi growing on the surface of saffron corms having different growth characteristics. Thirty corm samples having different growth characteristics, i.e., infected, unable to germinate, able to germinate but not bloom, able to germinate and produce one flower per corm, and able to germinate and produce two flowers per corm, were collected from South Tai Lake Agricultural Park, Huzhou central hospital. The next-generation sequencing (NGS) method was employed to detect the internal transcribed spacer (ITS) ribosomal RNA in fungus. The community structure of fungi on the surface of corms having different growth characteristics was described using bioinformatics tools, and the specific fungus on the corm surface was identified. The fungi on the surface of corms exhibited different developmental features. The abundance of Trichocomaceae and Talaromyces was high in infected corms, whereas that of Aspergillaceae was high in corms that were unable to germinate. Penicillium and Dothideomycetes were observed in corms that could germinate but not bloom, and in corms that could germinate and produce two flowers per corm, respectively. Differences were observed in Cladosporium, Lambertella, Passalora, Penicillium, and Talaromyces among the five groups at the genus level. An understanding of the fungal diversity on the corm surface might provide useful information for improving germination and blooming of saffron corms.